Hotel Management System - Core 2 (Booking, Reservation, Facilities Management, Customer / Guest Management and Customer Relationship Management): Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Hotels heavily depend on automated systems to facilitate efficient core transactions. Thesesystems are expected to be reliable and user-friendly and minimize human errors whileencoding data for all transactions. However, there is a problem with the current system interms of usability and security. Therefore, the goal of Core Transaction 2 is to address theseissues by developing a web-based system that is user-friendly for administrators andcustomers to access, input, process, and manage data. Additionally, this system will prioritizedata encryption to ensure the privacy and security of clients.The approach taken allowed the project team to create an improved Hotel ManagementSystem. It solved problems in booking, reservations, facilities management, and customermanagement by eliminating unnecessary processes, resulting in faster and better services forguests. The new feature, Core Transaction 2, will improve consistency and efficiency, leadingto productive employees and a better guest experience.The following objectives were achieved as a result of deploying this system, which improvedthe operations and capabilities of Core Transaction 2. 1. Develop a web-based system that isuser-friendly for administrators and customers to access, input, process, and manage data. 2.Integrated transactions into the other modules of the Hotel Management System to providesmooth, accurate, and efficient transactions. 3. Enhanced promotions management bycreating new promotions and advertising them through social media to attract potentialcustomers. 4. Enhanced customer management by creating a function that allows thecustomer to reach out to us with their concerns. 5. Enhanced security by providing dataencryption, email verification (OTP) for forgotten passwords, and user authentication. Inconclusion, the Hotel Management System - Core 2 presents features that simplify andautomate its primary operations and procedures, resulting in efficient management of thehotel's essential transactions.
Keywords: IT & Management